Обзор фауны и экологии пресноводных брюхоногих моллюсков (Gastropoda) западных областей Украины - Стадниченко, А.П. (Вестник зоологии, 1972)
Fauna, ecology and distribution of Gastropoda were studied in different natural-geographical zones in the western regions of the Ukraine. One species - Galba occulata Jackiewicz, 1959 new for the USSR fauna is found. For the first time two species are mentioned
mentioned for West-Ukrainian Polesie, two - for West-Ukrainian Forest Steppe, three - - for Forecarpathia, four - for the Ukrainian Carpathians and one - for Trans-carpathia. The characteristic o malacolauna of cach natural geographical zone is given, the data on mollusk ecology are presenled. In the fauna composition of Gastropoda the following zoogeographical groups can be distinguished: holarctic, paleoarctic, European-Siberiant, European, Baltic, West-European and Western Black Sea species.